Interaksi Dan Komunikasi Musikal Dalam Garap Sekaten - Bambang Sosodoro (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2018)
AbstractThe traditions that govern the music of gamelan Sekaten are commonly referred to as garap Sekaten. Based on observations of current musical practice, it can be comprehensively stated that garap Sekaten involves musical interaction and communication. This is reflected in the melodic phrases and interactive grammar between particular instruments of this ensemble. The characteristics, unique qualities, and complexities of garap sekaten have also influenced the gamelan ageng. For example, gendhing Bonang are a genre within gamelan ageng repertoire that accentuate the "loud" instruments and incorporate the sesegan/sabetan playing style found in garap Sekaten. This style is also adopted in particular gendhing Rebab in specific ways. Similarly, several instrumental techniques found in gamelan Ageng originate in garap Sekaten. These include imbal Demung, kinthilan, cegatan and nduduk tunggal techniques for Bonang, and salahan patterns for Kendhang. In short, an understanding of Garap Sekaten is one way of acquiring performance skills in individual instruments and gaining methods for interpreting certain gendhing.Â Key words: Garap Sekaten, Musical Interaction, Musical CommunicationÂ AbstrakTradisi atau kaidah-kaidah dalam praktik musikal gamelan sekaten lazim disebut garap sekaten. Berdasarkan fakta-fakta dan realitas praktik, secara komprehensif dapat dikatakan bahwa garap sekaten terdapat interaksi dan komunikasi musikal. Hal tersebut tercermin dalam kalimat lagu dan gramatikal permainan antar ricikan tertentu. Cirikhas, keunikan, dan kompleksitas garap sekaten juga berkembang di gamelan ageng. Seperti, gending-gending bonang yang menonjolkan instrumen bersuara nyaring, disertai garap sesegan/ sabetan. Garap sabetan yang melekat pada penyajian gending bonang, selanjutnya dikembangkan pada gending-gending rebab dengan ketentuan dan ciri-ciri tertentu. Juga teknik-teknik permainan ricikan, seperti imbal demung, kinthilan, teknik cegatan-nduduk tunggal pada bonangan, hingga pola salahan kendang. Singkatnya, garap sekaten dapat dipahami sebagai suatu tata cara yang memiliki karakteristik dalam menyajikan ricikan maupun mengintepretasi gending tertentu.Kata Kunci: garap sekaten, interaksi, komunikasi musikal